Menuju Satu Dekade Pelaksanaan Undang-Undang Desa - Silkanika Swarizona; Mi’rojul Huda (Journal on Education, 2023)
The village. development of the village continues to transform over time. The new direction of village development has begun seen since the 2014 Village Law, which has entered its 8th (Eight) year. Various innovations are seen as including the Village SDGs as a new paradigm of village development. This paper tries to review village development from time to time using descriptive qualitative methods. The village SDGs as a new paradigm of village development still leaves problems such as the capacity of the village head and village officials who are still unequal. There is lacking of performance accountability on transparency. Besides the data from the SDGs data collection that has not be able to enjoyed and felt by the village. Another problem with the village SDGs paradigm is the appearance of a large intervention from the higher instantion which is feared to reduce the principles of recognition and subsidiarity from